The Role of Consultative Selling in Enhancing Sales Performance: Evidence from Indibiz Digital Services - Muh. Febrianto Ahta Putra; Binarin Tiro Andika (Golden Ratio of Mapping Idea and Literature Format, 2026)
Low success rates in closing sales deals remain a major challenge in business-to-business (B2B) digital-service markets. This study aims to analyze the implementation of the consultative selling approach in the sales process of Indibiz digital services and examine its role in enhancing the sales performance. This study employs a qualitative approach, with data collected through observation and in-depth interviews with informants involved in sales activities, supported by company documentation. Data validity was ensured through triangulation techniques, and data analysis was conducted through data reduction, data display, and conclusion drawing. The findings show that consultative selling helps sales personnel better understand customer needs, identify business problems, and provide relevant solutions to them. This approach plays an important role in building customer trust and increasing the likelihood of closing sales. In addition, it supports long-term relationships through continuous communication and post-sale assistance. However, several challenges remain, including complex decision-making processes in B2B markets and inconsistent implementation among salespeople. Therefore, future research should explore its application in different industries and combine qualitative and quantitative approaches to better understand its impact on sales performance.